2017
DOI: 10.1016/j.ijrobp.2017.06.2452
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Survival After Combining Thoracic Irradiation and an Anti-PD-1 Antibody Correlated With Increased T-cell Infiltration Into Cardiac and Lung Tissues

Abstract: Purpose Lung cancer is the leading cause of cancer-related mortality in the United States. Radiation, a common component of treatment, can cause acute damage to critical organs including the lungs and the heart, but the serious toxicities from radiotherapy alone is relatively rare. A recent addition to the treatment regimen is immunotherapy, such as anti-PD-1 antibody, which blocks the inhibition of activated T cells. Combining anti-PD-1 treatment and thoracic radiation has potential for improving the outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…This kind of secondary effect could be related to a T-cell infiltration of the esophagus according to the hypothesis proposed by Myers and Du, after having exposed murine preclinical model to the therapeutic combination. 28,29 In their studies, T-cell counts were significantly elevated in both cardiac and pulmonary tissues after combination therapy as compared to treatment with radiation alone, indicating that, while prolonging the action of immune cells may enhance their antitumor activity, nonmalignant tissue damaged by irradiation is susceptible to accumulation of and further damage by activated T cells. It could be one of the limits of this treatment combination in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of secondary effect could be related to a T-cell infiltration of the esophagus according to the hypothesis proposed by Myers and Du, after having exposed murine preclinical model to the therapeutic combination. 28,29 In their studies, T-cell counts were significantly elevated in both cardiac and pulmonary tissues after combination therapy as compared to treatment with radiation alone, indicating that, while prolonging the action of immune cells may enhance their antitumor activity, nonmalignant tissue damaged by irradiation is susceptible to accumulation of and further damage by activated T cells. It could be one of the limits of this treatment combination in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mortality and cardiac dysfunction (illustrated by reduced ejection fraction) were observed in mice receiving cardiac RT with PD-1 blockade versus mice that only received RT [185]. Myers and Lu treated C57BL/6 mice with whole thorax irradiation in combination with an anti-PD-1 antibody and also observed reduced survival and increased numbers of T-cells in lung and heart compared to radiation alone [186]. These studies have shown that radiation-induced cardiac toxicity can be altered by PD-1 through cytotoxic T lymphocytes and suggest that PD-1 blockade should be administered with purposeful cardiac RT planning to ensure both positive treatment outcome and patient safety.…”
Section: Radiation Therapy and The Immune Responsementioning
confidence: 99%
“…Du et al demonstrated with C57Bl/6 mice that whole-heart RT with PD-1 blockade led to increased mortality and cardiac dysfunction compared to mice that were only given cardiac RT [66]. With respect to the immune cell subtypes present, Myers and Lu saw increased mortality, as well as an increase in number of T cells, in the lungs and heart of C57Bl/6 mice that received thoracic RT and an anti-PD-1 antibody compared to mice given thoracic RT [67]. These findings suggest an enhanced sensitivity to cardiac RT when the immune system, specifically cytotoxic T lymphocytes, is no longer suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…Recent advances in combinational cancer therapies, where the patient may receive radiation, as well as immunotherapy, hold great promise. In light of this, there is increasing interest in understanding how immunotherapy, including checkpoint inhibitors, could alter the effects of RT on the heart [66,67]. Radiation can alter immune responses, and the effects of radiation can change based on the state of both adaptive and innate immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation